2005
DOI: 10.1016/j.asj.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous autoinflation of saline mammary implants: Further studies

Abstract: There are multiple macromolecules that cross into the lumen of the prosthesis. We believe spontaneous autoinflation is occurring more often than is believed or reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Late seroma after silicone breast implants Robinson et al 13 observed 14 cases of spontaneous enlargement in 3,000 patients with saline implants. Fluid cultures were all negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Late seroma after silicone breast implants Robinson et al 13 observed 14 cases of spontaneous enlargement in 3,000 patients with saline implants. Fluid cultures were all negative.…”
Section: Discussionmentioning
confidence: 99%
“…Late seromas after breast implants have developed after both silicone 6,9,15 and saline implant placement 7,13,14 . In silicone implants, the fluid accumulates outside the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Intraprosthetic collection of fluid or sterile pus though not very common has been reported both in saline as well as silicone gel implants. [11][12][13][14] However the process differs in the two instances. In saline implants, the shell allows passage of protein macromolecules, predominantly albumin that creates an osmotic gradient across the macroscopically intact silicone shell allowing body fluids to enter the prosthesis.…”
Section: Intraprosthetic Collection Of Fluid Presenting As Autoinflatmentioning
confidence: 99%
“…No extracapsular fluid collection has been reported with the process concerning saline implants. [14] On the contrary, intraprosthetic collection of fluid in silicone gel implant is almost always associated with damaged or ruptured shell that may or may not be macroscopically visible and there is almost always intracapsular collection of fluid or sterile pus at the same time. [11][12][13] The damaged shell allows intracapsular fluid to gain access to the inside of the damaged implant resulting in autoinflation of the breast.…”
Section: Intraprosthetic Collection Of Fluid Presenting As Autoinflatmentioning
confidence: 99%
See 1 more Smart Citation